Voltage detected single spin dynamics in diamond at ambient conditions - Sergei Trofimov; Klaus Lips; Boris Naydenov (Nature Communications)
Abstract Defect centres in crystals like diamond or silicon find a wide application in quantum technology, where the detection and control of their quantum states is crucial for their implementation as quantum sensors and qubits. The quantum information is usually encoded in the spin state of these defect centres, but they also often possess a charge which is typically not utilized. We report here the detection of elementary charges bound to single nitrogen-vacancy (NV) centres several nanometres below the diamond surface using Kelvin Probe Force Microscopy (KPFM) under laser illumination. Moreover, the measured signal depends on the NV’s electron spin state, thus allowing to perform a non-optical single spin readout, a technique we refer to as “Surface Voltage Detected Magnetic Resonance” (SVDMR). Our method opens a way of coherent spin dynamics detection for quantum sensing applications and could be potentially applied to other solid state systems. We believe that this voltage-based readout would help to simplify the design of devices for quantum technology.